PERANCANGAN SISTEM PEMBELAJARAN MOBILE (M-LEARNING) BERBASIS ANDROID PADA MATERI BANGUN DATAR DAN BANGUN RUANG - Tedi Budiman (Jurnal Accounting Information System (AIMS), 2018)
One example of the growing information technology today is mobile learning, mobile learning which refers to mobile technology as a learning medium. Mobile learning is learning that is unique for each student to access learning materials anywhere, anytime. Mobile learning is suitable as a model of learning for the students to make it easier to get an understanding of a given subject, such as math is pretty complicated and always using formulas.The design method that I use is the case study method, namely, learning, searching and collecting data related to the study. While the development of engineering design software application programs that will be used by the author is the method of Rapid Application Development (RAD), which consists of 4 stages: Requirements Planning Phase, User Design Phase, Construction Phase and Phase Cotuver.